COMPARATIVE ANALYSIS OF PLASTERING WORK EXECUTION TIME ON LABOUR PRODUCTIVITY WITH WORK SAMPLING METHOD - Susanti, Dwi Dzulma; Supriani, Fepy; Misliniyati, Rena; Mase, Lindung Zalbuin; Hardiansyah (Jurnal Pensil : Pendidikan Teknik Sipil, 2025)
Labor productivity is the main parameter in the success of a construction job. This study aims to analyze the level of productivity and the level of Labor Utilization Rate (LUR) in plastering work using the work sampling method, and the most effective time correlation between morning and afternoon. This research was conducted by direct observation for 3 days. The results showed that the highest productivity value was 14.30 m²/hour in the afternoon, and the lowest productivity value was 6.86 m²/hour in the morning. The Labor Utilization Rate (LUR) values in the morning and afternoon were 57.9% and 65.9%, indicating that the afternoon time was more effective than the morning time. However, there was a significant difference in productivity between morning and afternoon time overall, and it can still be categorized as effective with a Labor Utilization Rate (LUR) value of 61.9%, which exceeds 50%.